Happy St. Patrick's Day from the crayons - Daywalt, Drew (Philomel, 2024)
"As St. Patrick's Day fast approaches, Green Crayon would like a break since he's still recovering from Christmas, but when his friends try to take over, it soon becomes apparent just how much he's needed"--